Antihypertensive therapy in diabetic patients - António, Sandra (2008)
Diabetes mellitus and hypertension are clinical entities frequently combined in the same patient; together they exert a synergetic effect that causes, among other events, a fast deterioration of the kidney function and a growing cardiovascular risk. The diabetic patients blood pressure must be strictly controlled, aiming at values inferior to 130/80 mmHg. Goals: The analysis of the classes of antihypertensives more frequently recommended for the treatment of the hypertensive diabetic patient. Methods: Bibliographic review, including reference studies and recently published articles on the areas of Diabetology and Hypertension. Conclusions: The first choice antihypertensives should be ACE inhibitors, due to their protective effects on the kidney and the cardiovascular system. In case of intolerance or counter-indication to these antihypertensives, the therapeutic choice should fall on angiotensin II receptor antagonists, which may be combined with low dosage thiazide diuretics. On a second row of the therapeutic arsenal stand b-blockers and calcium channel blockers. Loop diuretics, central agents and a-blockers are third line drugs destined for use in cases of hypertension that resists to the previous classes and/or in specific cases.